2009
DOI: 10.1088/1468-6996/10/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antibacterial properties of Ag nanorods by electric field

Abstract: The effect of an electric field on the antibacterial activity of columnar aligned silver nanorods was investigated. Silver nanorods with a polygonal cross section, a width of 20-60 nm and a length of 260-550 nm, were grown on a titanium interlayer by applying an electric field perpendicular to the surface of a Ag/Ti/Si(100) thin film during its heat treatment at 700• C in an Ar+H 2 environment. The optical absorption spectrum of the silver nanorods exhibited two peaks at wavelengths of 350 and 395 nm correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Akhavan et al [18,19] reported two studies about the antibacterial effect of silver, one in which an electric field was applied in the direction of silver nanorods grown on a Ti interlayer deposited by dc magnetron sputtering, and another which reported compact Ag nanorods capped by sol-gel mesoporous TiO 2 layer, both deposited onto silicon substrates. The two studies showed a strong, fast and lasting antibacterial activity against Escherichia coli (E. coli).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Akhavan et al [18,19] reported two studies about the antibacterial effect of silver, one in which an electric field was applied in the direction of silver nanorods grown on a Ti interlayer deposited by dc magnetron sputtering, and another which reported compact Ag nanorods capped by sol-gel mesoporous TiO 2 layer, both deposited onto silicon substrates. The two studies showed a strong, fast and lasting antibacterial activity against Escherichia coli (E. coli).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent times owing to advancement of some resistant bacterial strains to counter the antibiotics, the antibacterial activity of nanomaterials, such as zinc, silver and copper, with their unique size dependent properties has attracted great attentions [1][2][3][4][5]. For instance, ZnO with a quartzite hexagonal phase have a direct band gap of 3.37 eV possesses a wide range of technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, before anything, silver itself is known as one of the most interesting antibacterial materials [17,[33][34][35][36][37]. It is generally believed Ag + can bind to bacterial cell wall membrane (slightly negative), damage it and so alter its functionality [38][39][40].…”
Section: Introductionmentioning
confidence: 99%